Determination of MS Location through Building Using AoA Method of Frequency 47 GHz - Andrita Ceriana Eska (IJITEE (International Journal of Information Technology and Electrical Engineering), 2018)
This research discusses the determination of mobile station (MS) location of the uplink communication system. The location determination mobile station is based on the angle-of-arrival (AoA) method. The communication propagation is influenced by building environment. The building environment was modeled with diffraction method. Several diffraction methods were used such as single knife edge, and multiple knife edge method. The communication frequency used was 47 GHz. The analysis used percentage value at coverage area and comparison of error percent values between two method to determine mobile station location. The percentage of the communication coverage area obtained was 71.4% or of 255 from 300 nodes. The comparison methods used for mobile station location determination were the selection of the best SNR and localization technique. The error percentage value based on the selection of the best SNR method is 0.95%. The error percentage value based on localization technique method is 0.78%.